Cummings otolaryngology-head and neck surgery - Flint, Paul W.; Haughey, Bruce H; Lund, Valerie J; Robbins, K Thomas; Thomas, J Regan; Lesperance, Marci M; Francis, Howard W (Elsevier, 2021)
"Extensive coverage of all aspects of otolaryngology and head and neck surgery"-- Provided by publisher.